High-tech marketing: Challenges and opportunities for the Russian Federation - I. V. Alyoshina (Управление)
The purpose of the study is to search for guidelines for holistic marketing in solving the problems of high-tech development of the Russian economy. The article reveals the problems and opportunities of marketing for high-tech solutions in the Russian realities of the world economy geopolitical crisis period, sanctions pressure and the disruption of global innovation links. The results of statistical and expert evaluations of the Russian and foreign studies are analyzed. Approaches to the definition of high technologies are presented; their features as an object of marketing (complexity, high uncertainty of results), as well as demand and competition; high risks of investments of all types of resources. The innovativeness, ability to generate and commercialize high-tech innovations crossing the boundaries of industries, cultures and markets of the regions of the world, is defined as a necessary condition for sustainability, competitiveness of the economy and the potential for its development. The definition of high-tech marketing in the concept of holistic marketing is proposed. High level of human capital development in the Russian Federation is defined as a prerequisite for the use of creative solutions in marketing of high-tech innovations. The recommendations of marketing solutions for the deployment of the life cycle of a high-tech product for market segments of varying degrees of maturity are presented, the methods and models used in high-tech marketing are indicated. The importance of informing and educating a wide and professional audiences is emphasized. High technologies are proposed to be considered as part of innovative systems in the context of socio-economic institutions. It is noted that the holistic concept of high technology marketing as an element of national, technological and global innovation systems involves decisions at the institutional and infrastructural levels.